Causal Factors Affecting the Effectiveness of Police Volunteers in Thailand - วีริยาสรร พลตำรวจตรี รมย์สิทธิ์ (The Journal of Development Administration Research, 2015)
The research aimed to study Causal Factors Affecting the Effectiveness of Police Volunteers. The quantitative research employed a questionnaire given to a sample of 362 participants from police officers working as community police and the commission of overseeing and following-up police administration. The statistical analysis included descriptive statistic, confirmatory factor analysis and path analysis through use of LISREL program. The research revealed that factors affecting the performance effectiveness of police volunteers were their personal characteristic factors, public participation factors and management factors. The result showed that public participation factors were the most influent factor affecting the performance effectiveness of police volunteers followed by management factors and personal characteristic factors of the police volunteers respectively.